DNA polymerase η mutational signatures are found in a variety of different types of cancer. Issue 3 (1st February 2018) - Rogozin, Igor B.; Goncearenco, Alexander; Lada, Artem G.; De, Subhajyoti; Yurchenko, Vyacheslav; Nudelman, German; Panchenko, Anna R.; Cooper, David N.; Pavlov, Youri I.
ABSTRACT: DNA polymerase (pol) η is a specialized error-prone polymerase with at least two quite different and contrasting cellular roles: to mitigate the genetic consequences of solar UV irradiation, and promote somatic hypermutation in the variable regions of immunoglobulin genes. Misregulation and mistargeting of pol η can compromise genome integrity. We explored whether the mutational signature of pol η could be found in datasets of human somatic mutations derived from normal and cancer cells. A substantial excess of single and tandem somatic mutations within known pol η mutable motifs was noted in skin cancer as well as in many other types of human cancer, suggesting that somatic mutations in A:T bases generated by DNA polymerase η are a common feature of tumorigenesis. Another peculiarity of pol ηmutational signatures, mutations in YC G motifs, led us to speculate that error-prone DNA synthesis opposite methylated CpG dinucleotides by misregulated pol η in tumors might constitute an additional mechanism of cytosine demethylation in this hypermutable dinucleotide.